Percutaneous catheter-directed treatment in intermediate-high risk acute pulmonary embolism. Hemodynanical and right heart function-related parameters changes and short-term outcomes - Gradoli Palmero, J (Eur Heart J Acute Cardiovasc Care, 2021)
FUNDING ACKNOWLEDGEMENTS: Type of funding sources: None. Introduction Acute pulmonary embolism (PE) is the third cause of cardiovascular mortality, right after acute myocardial infarction and stroke. Systemic thrombolytic therapy (SLT) restores pulmonary perfusion earlier than low molecular-weight heparin, but with a significantly higher risk of major bleeding. Currently, in our area there is a lack of standardized protocols for the management of patients in which SLT is contraindicated.  Objective The purpose of our study was to evaluate the safety and efficacy of percutaneous catheter-directed treatment (PCT) for high-intermediate risk PE (HIRPE) patients with hemodynamic deterioration on anticoagulation treatment. Methods We consecutively included all patients with HIRPE patients who underwent PCT in our center. Before and after PCT clinical, echocardiographic and hemodynamic variables were collected, as well as events (major or minor bleeding, death) during follow-up. Results From February 2018 to February 2020, 20 patients with HIRPE underwent PCT. The mean age of our cohort was 62 (52 - 73), and 46.6% were women. The indication for PCT was absolute contraindication for SLT (9 patients, 45%), followed by high bleeding risk (8 patients, 40%) and failure of SLT. Vascular access was mainly performed through femoral vein (12 patients, 60%) followed by a peripheral vein of the superior limb (8 patients, 40%). During pulmonary angiography, lobar arteries occlusion was observed in 60% of the cases, with involvement of main pulmonary arteries in 40% of the cases. Local thrombolysis with Alteplase was performed in 17 cases (85%), and in 8 cases it was decided to carry-out a thrombus fragmentation-aspiration strategy. We observed and early improvement of hemodynamic parameters after PCT, with a significant reduction of mean pulmonary artery pressure before and after PCT (40 +/- 13 mmHg vs. 25 +/- 12 mmHg, p < 0.001, figure 1), as well as an improvement in systolic blood pressure (102 +/- 13 mmHg vs. 129 +/- 14, p < 0.001) and the partial pressure of oxygen (51 +/- 3 vs. 67 +/- 2, p = 0.002). We also observed a significant decrease in NT-proBNP values at admission and 48 hours after PCT (4791 +/- 1077 pg/mL vs. 2311 +/- 680 pg/mL, p = 0.002, figure 2), as well as an improvement in echocardiographic right ventricular function parameters evaluated at admission and 72 hours after PCT, such as TAPSE (15 +/- 2 mm vs 22 +/- 3 mm, p = 0.001) or right ventricle basal diameter (51 +/- 4 mm vs. 41 +/- 2 mm, p = 0.001). During a median follow-up of 7 months (4 - 12 months) one patient died of non-cardiac cause and none of them had a major or minor bleeding event. CONCLUSION: PCT in patients with HIRPE with hemodynamic deterioration on anticoagulation is a simple and effective procedure with an immediate reduction of mean pulmonary pressure and an early improvement of right ventricle-related biochemical, hemodynamic and echocardiographic parameters.